HNF1β‐associated cyst development and electrolyte disturbances are not explained by BAIAP2L2 expression. Issue 1 (15th December 2022) - Tholen, Lotte E.; Schigt, Heidi; Kleuskens, Sanne G. E.; Bos, Caro; Spruijt, Cornelia G.; Willemsen, Brigith; Vermeulen, Michiel; Hoenderop, Joost G. J.; de Baaij, Jeroen H. F.
Abstract: Mutations or deletions in transcription factor hepatocyte nuclear factor 1 homeobox β (HNF1β) cause renal cysts and/or malformation, maturity‐onset diabetes of the young and electrolyte disturbances. Here, we applied a comprehensive bioinformatic approach on ChIP‐seq, RNA‐seq, and gene expression array studies to identify novel transcriptional targets of HNF1β explaining the kidney phenotype of HNF1β patients. We identified BAR/IMD Domain Containing Adaptor Protein 2 Like 2 ( BAIAP2L2 ), as a novel transcriptional target of HNF1β and validated direct transcriptional activation of the BAIAP2L2 promoter by a reporter luciferase assay. Using mass spectrometry analysis, we show that BAIAP2L2 binds to other members of the I‐BAR domain‐containing family: BAIAP2 and BAIAP2L1. Subsequently, the role of BAIAP2L2 in maintaining epithelial cell integrity in the kidney was assessed using Baiap2l2 knockout cell and mouse models. Kidney epithelial cells lacking functional BAIAP2L2 displayed normal F‐actin distribution at cell–cell contacts and formed polarized three‐dimensional spheroids with a lumen. In vivo, Baiap2l2 knockout mice displayed normal kidney and colon tissue morphology and serum and urine electrolyte concentrations were not affected. Altogether, our study is the first to characterize the function of BAIAP2L2 in the kidney in vivo and we report that mice lacking BAIAP2L2 exhibit normal electrolyte homeostasis and tissue morphology under physiological conditions.